ANALISIS IMPLEMENTASI CASHLESS SYSTEM BERBASIS FINGERPRINT DALAM MENINGKATKAN KEDISIPLINAN KEUANGAN SANTRI - Didin Burhanudin Rabbani; Erlina Agustin; Qurratul Kamilia (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2026)
The development of financial digitalization today encourages Islamic boarding schools (pesantren) to adopt more effective and efficient financial service systems. The presence of a fingerprint-based cashless system serves as a form of modernization and enhancement of financial transparency in pesantren, which typically involve numerous economic activities. This study aims to examine and analyze the benefits, implications, and challenges of implementing a fingerprint-based cashless system in improving students’ financial discipline. This research employs a descriptive qualitative method by conducting observations, documentations, and interviews with students and the management of TMI Al-Amien Prenduan as direct users of the fingerprint-based cashless system in their daily payment activities. The findings indicate that the fingerprint-based cashless system simplifies students’ daily transactions, increases the efficiency of pesantren financial services, strengthens transparency, and enhancing discipline in the financial management of the students. The system also enables more accurate and structured financial monitoring, particularly for parents or guardians who can directly track their children’s spending activities through an application integrated into their mobile devices. However, several challenges persist, including the risk of consumptive behavior due to transaction convenience, limited digital literacy among some students, and data security issues that require serious attention. Overall, the implementation of the fingerprint-based cashless system is considered effective in supporting the modernization and accountability of pesantren financial management. Its successful implementation of fingerprint-based cashless requires support in financial literacy, consumption pattern education, and the application of Islamic economic principles to create a safe and proportional financial digitalization. Keywords: cashless system; financial discipline; student.